2011
DOI: 10.1007/s10661-011-2167-7
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity assessment of contaminated soil in the vicinity of industrial area

Abstract: In the industrial area of Chinhat, Lucknow (India) wastewater coming from pesticide manufacturing and other industries is used to irrigate the agricultural crops. This practice has been polluting the soil and pollutants might reach the food chain. Gas chromatographic analysis revealed the presence of certain organochlorine pesticides in soil samples. Samples were extracted using different solvents, i.e., hexane, acetonitrile, methanol, chloroform, and acetone (all were HPLC-grade, SRL, India). Soil extracts we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Numerous workers observed that in XAD concentrated extracts, TA98 strain was more responsive compare to TA100 in both with and without S9 fraction, moreover extracted concentration of XAD was also more mutagenic than the samples of liquid-liquid extraction, as reported by several workers [8,49]. Wastewater discharge from industrial area of Lucknow (pesticide industry) is used for irrigation purposes and the soil irrigated with wastewater showed strong mutagenic activity in comparison to soil irrigated with ground water [50].…”
Section: Discussionmentioning
confidence: 95%
“…Numerous workers observed that in XAD concentrated extracts, TA98 strain was more responsive compare to TA100 in both with and without S9 fraction, moreover extracted concentration of XAD was also more mutagenic than the samples of liquid-liquid extraction, as reported by several workers [8,49]. Wastewater discharge from industrial area of Lucknow (pesticide industry) is used for irrigation purposes and the soil irrigated with wastewater showed strong mutagenic activity in comparison to soil irrigated with ground water [50].…”
Section: Discussionmentioning
confidence: 95%
“…Contrary to this situation 1-formulation, using saline:Tween 80 (4:1, v/v), expressed lower or similar mutagenic frequency at much higher doses (Figure 3). Additionally, the mutagenic potentials, defined as the slope of the initial linear portion of each doseresponse curve, [43] were lower when 1 was vehicled in saline: Tween 80 (Figure 4).…”
Section: In Vitro-and In Vivo-genetic Toxicitymentioning
confidence: 99%
“…Mutagenicity was assessed for the crops irrigated with wastewater from pesticide manufacturing and other industries within the area of Chinhat, India, which contained organochlorine pesticides (Anjum and Malik, 2012). The authors concluded that the soil that irrigated with the wastewater were polluted and had relatively higher mutagenicity levels than groundwater-irrigated soil had.…”
Section: Authors Found the Probability Of Infection Bymentioning
confidence: 99%